The Spiritual Well-Being of Elderly People: A Study of a French Sample - Velasco-Gonzalez, Lucy (Journal of religion and health, 2014)
The aim of our research was to identify predictors of the spiritual well-being of elderly people. More specifically, we postulated that subjective well-being and its components would be predictors of spiritual well-being, and more so than age and health status. We invited 133 people aged 60-95 to complete a questionnaire that included the French adaptation (Velasco and Rioux in Revue Canadienne des Sciences du Comportement 41(2):102-128, 2009) of Paloutzian and Ellison's (Loneliness: A sourcebook of current theory, research and therapy, Wiley-Interscience, New York, 1982) Spiritual Well-Being Scale, Ryff and Essex's (Psychol Aging 7:507-517, 1992) Psychological Well-Being Scale (translated by Lapierre and Desrochers 1997), Salamon and Conte's (Meas Eval Guid 15(3):194-200, 1982) Life Satisfaction in the Elderly Scale (validated by Rousseau and Dubé in 1993), and the French version (Blais et al. in Can J Behav Sci 21:210-223, 1989) of Diener et al. (J Pers Assess 49:71-75, 1985) Satisfaction with Life Scale. The results only partially confirm our hypothesis, because only satisfaction with life as a whole and two items in "Life Satisfaction in the Elderly Scale" make it possible to predict the spiritual well-being of elderly people. Moreover, neither health status nor age was found to be a significant predictor of spiritual well-being. This research helps understand better the links between the concept of spiritual well-being and that of subjective well-being of elderly people and could contribute to the development of a tool that could take into account the spiritual well-being of elderly people, whether they be believers, agnostic, or atheist.